Factors that influence tax auditors’ conciliatory style in resolving disputes: Pre-test and pilot study - Nordin, Zarifah Syahirah; Muhammad, Izlawanie (2015)
The purpose of this study is to examine the validity and reliability of the questionnaire which serve as a research instrument.The validity of the instrument can be viewed by using the content validity that is conducted during pre-test which involves evaluation by experts in the subject area of study While, the reliability of the instrument can be seen through pilot study. Pilot study involved with a small scale of respondents where it is used to determine whether the instrument are reliable, whether the respondent has a clear understanding on questions in the questionnaire and it is conducted prior to real study.A total of 50 sets of questionnaire had been distributed to investigators from Inland Revenue Board of Malaysia (IRBM) in Jalan Duta branch. Out of these, only 21 completed questionnaires were returned.The data then was keyed in and analysed using SPSS software version 21. The results from reliability analysis revealed that Cronbach’s alpha value for all variables (attitudes towards achieving goals, experience, ethical ideologies, managerial control and tax auditors’ conciliatory style) are more than cut-off point that is 0.70. This can be concluded that the instrument is reliable and none of the items have to be deleted.